The Articulated Nutritional Program and its impact on chronic malnutrition in children under five years of age. Dirección Regional de Salud Callao, 2009-2015 - Shajian-Torres, Keila (2020)
Objective: To determine the impact of the Articulated Nutritional Program (PAN) on chronic malnutrition in children under five years of age, its correlation with the PAN’s budget execution, and the prevalence of chronic malnutrition at the Dirección Regional de Salud (DIRESA) Callao, 2009-2015. Materials and methods: A quantitative, qualitative, observational, ecological, correlational, longitudinal and retrospective study was carried out. The Pearson correlation coefficient was determined in the quantitative analysis. Qualitative data was obtained from in-depth interviews with the support of a semi-structured guide. Results: There is no relationship between the PAN’s Modified Institutional Budget (PIM) and the prevalence of chronic malnutrition (p value 0.92). There is no relationship between the budget execution of the PIM and the prevalence of chronic malnutrition (p value 0.355). The factors that influenced the execution of the PAN are untimely budget, delayed implementation of the PAN, difficulties in the organization of health services, and population with little education on child and migrant care. Conclusions: No positive impact was found between the PAN and the decrease in the prevalence of chronic malnutrition at the DIRESA Callao between 2009 and 2015. The qualitative factors that influence the PAN were related to processes and the organization of the DIRESA Callao, with the exception of the population corresponding to an external factor.